Archipelag Senkaku. Źródło napięć na Morzu Wschodniochińskim - Kaczmarek, Piotr (Wydawnictwo Naukowe WNPiD UAM, Poznań, 2012)
The article analyzes the question of Senkaku islands dispute between Japan, China and Taiwan. The aim of the text is to present how the dispute has affected Japan-China bilateral relations. At first, the paper focuses on characterization: the subject of dispute, claims of countries, its course and an international aspect. The second part considers: the incident in September 2010 and its consequences, the dispute effects and prosperities of its regulations. The relations between China and Japan are very complicated. The Senkaku Islands dispute and 2010 incident are presently one of the most important reasons for disagreement.
Senkaku Islands. The Source of Tension in the East China Sea
Keywords: Archipelag Senkaku; Morze Wschodniochińskie; Chiny; Japonia; Tajwan